Implementation of Corporate Social Responsibility in Improving the Welfare of the Surrounding Community (Case Study On PT Juyomi Sinar Labuan) - Liana; Sugianto; Abdul Kahar; Latifah Sukmawati Yuniar (GoodWill Journal of Economics, Management, and Accounting, 2025)
This study aims to evaluate the implementation of the Corporate Social Responsibility (CSR) program carried out by PT Juyomi Sinar Labuan and its impact on the welfare of the surrounding community. The research uses a qualitative approach with a case study method, through interviews, observations, documentation, and literature studies. The results of the study show that the implementation of PT Juyomi's CSR includes three main aspects, namely social, economic, and environmental. In the social sector, PT Juyomi facilitates free health services, ambulance assistance, education funds, support for religious activities, and distribution of basic necessities. In the economic sector, the company prioritizes recruiting local workers, providing interest-free loans to employees, and distributing village empowerment funds. Meanwhile, in the environmental aspect, the company routinely carries out reforestation and hands over industrial waste management to third parties. Although CSR programs have had a positive impact on people's welfare, some obstacles still arise, such as lack of transparency of information and negative environmental impacts in the form of reduced spring water sources due to mining activities. This research was conducted at PT Juyomi Sinar Labuan which is located at Jl. Taragengge, Labuan Lelea Village, Labuan District, Donggala Regency, Central Sulawesi. These findings show that the implementation of CSR contributes significantly to the socio-economic development of the community, but it needs to be improved in terms of sustainability and information disclosure.